The role of experiential avoidance, belonging and psychological well-being in predicting university students’ digital game addiction - Akbaba, Dilan; Çetinkaya Yıldız, Evrim (Journal of Dependence, 2024)
Objective: This study explores how gender, experiential avoidance, belongingness, and psychological well-being influence university students’ digital game addiction. Method: The study participants were 392 undergraduate students, 217 female and 175 male, who played digital games and consented to join the study. The researchers used the following instruments: “Personal Information Form”, “Digital Game Addiction Scale for University Students”, “Acceptance and Action Form II”, “Belonging Scale”, and “Psychological Well-Being Scale”. Results: The regression analysis showed that the model with gender, experiential avoidance, belongingness, and psychological well-being variables was statistically significant in predicting the digital game addiction scores of university students. The model accounted for 14.4% of the total variance of digital game addiction. Conclusion: The study found that gender and experiential avoidance scores were significant predictors of digital game addiction scores. The study suggests developing and implementing psyco-educational and/or encounter groups programs to lower the experiential avoidance levels of university students and to prevent digital game addiction among male university students.